Redesain Kemasan Makanan Ringan Olahan pada UMKM Center Jawa Tengah dengan Metode Kansei Engineering - Susatyo Nugroho; W, Darminto Pujotom; M. Mujiya Ulkhaq; Dedy Teguh Permadi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
UMKM (Micro, Small, and Medium Enterprises) Center in Central Java Province has 69 types of potential culinary products in the form of snacks. An initial study showed that from 47 MSMEs, there are 45 products which are packaged simply. The research was conducted to create a new packaging design which is appropriate for consumers' needs using Kansei Engineering. The method translates consumers' psychological feelings into new packaging design parameters as well as statistics analysis to elicit design elements in accordance with Kansei Word. Affective and psychological aspects that affect consumers on product packaging are